2021
DOI: 10.3390/genes12020131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum and Genetic Diagnosis of 54 Consecutive Patients Aged 0–25 with Bilateral Cataracts

Abstract: Childhood cataract affects 2.5–3.5 per 10,000 children in the UK, with a genetic mutation identified in 50–90% of bilateral cases. However, cataracts can also manifest in adolescence and early adulthood in isolation, as part of a complex ocular phenotype or with systemic features making accurate diagnosis more challenging. We investigate our real-world experience through a retrospective review of consecutive bilateral cataract patients (0–25 years) presenting to the ocular genetics service at Moorfields Eye Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…These examples may reflect ethnic biases in gene discovery efforts and control cohorts to date. Some studies have reported different diagnostic rates in sporadic compared to familial cases, 52 whereas others found no difference 30 . It is likely that all these factors as well as differences in disease definitions and inclusion criteria combined with stochastic effects inherent in small studies contribute to the differences.…”
Section: Diagnostic Rates For Genomic Testing In Ophthalmologymentioning
confidence: 99%
See 2 more Smart Citations
“…These examples may reflect ethnic biases in gene discovery efforts and control cohorts to date. Some studies have reported different diagnostic rates in sporadic compared to familial cases, 52 whereas others found no difference 30 . It is likely that all these factors as well as differences in disease definitions and inclusion criteria combined with stochastic effects inherent in small studies contribute to the differences.…”
Section: Diagnostic Rates For Genomic Testing In Ophthalmologymentioning
confidence: 99%
“…In contrast, and more recently, several studies show that for IRDs, which are highly heterogeneous, a well‐curated panel provides greater sensitivity and diagnostic yield than WES, 27,28 and multiple studies demonstrate that panels are able to detect pathogenic variants for some patients in genes not primarily associated with the phenotype 15,27,28 . However, the diagnostic rate varies greatly with phenotypes and is in the range 25%–64% for most studies of varied phenotypes 13,20,24–28,30 . This may be improved with more homogeneous phenotype classification and more considered target panel selection, 21,22,31 but there will remain as substantial number of patients likely requiring additional investigations by WES or WGS to expand the genes tested.…”
Section: Massively Parallel Sequencing For Genomic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataracts have a wide differential diagnosis, including maternally derived infections, iatrogenic, and trauma. However, a molecular cause can be identified for the majority of patients in 1 of 115 associated genes [14,[16][17][18]. Inherited cataracts most commonly occur on their own (70%), but patients may also present with associated ocular (15%) and systemic features (15%).…”
Section: Introductionmentioning
confidence: 99%
“…Inherited cataracts most commonly occur on their own (70%), but patients may also present with associated ocular (15%) and systemic features (15%). Common additional ocular features include anterior segment dysgenesis, retinal dystrophies, aniridia, and microphthalmia (defined as a small underdeveloped eye, with an axial length of more than two standard deviations below the age adjusted mean) [18,19]. Microphthalmia with cataracts have been associated with mutations in CRYAA, CRYBA4, CRYBB1, CRYBB2, CRYGC, CRYGD, GJA3, FOXE3, PITX3, IPO13, SIPA1L3, VSX2, GJA8, and NHS [16,[20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%